Multiple-Music Versions?: A German Sound Film-Operetta and Its Versions for France and Italy. - ZECHNER, INGEBORG (Music, Sound & the Moving Image)
With the advent of sound film in the early 1930s the German film industry produced so-called multiple-language versions as a part of its internationalisation strategy. These versions were produced for the French, English, and Italian markets (often) with a new cast of actors. Despite the importance of music in these films, a systematic study on the role of music in these multiple-language versions is still lacking. This article offers a first case study on the topic by comparing the German, Italian, and French versions of the sound film-operetta Paprika (1932/1933). It will be illustrated that the music (rather than sound) as well as the use of the musical material in the versions of Paprika differed significantly. Musical adaptation was used as an important means to shape the film's narrative and to create a distinct aesthetic for each of the film's versions. Historically, there are evident parallels to the adaptation practice of opera and operetta over the past centuries.